Tingkat Dukungan Orang Tua Terhadap Belajar Siswa - Juster Donal Sinaga (Universitas Mathla'ul Anwar Banten, 2018)
THE LEVEL OF PARENTS SUPPORT TO LEARN CHILDREN. This study aims to describe the level of parents support to learn children. The results of this study serve as the basic design of home visit services as one way to improve the parent support system in learning children. This research is a quantitative research. The subjects of this study were students of grade VIII at SMPN 31 Purworejo which amounted to 31 students. The research data was collected using Parent/Guardian Support Questionnaire to Child Learning and Questionnaire of Child's Opinion on Support of Parent/Guardian developed by the researcher from Ariffin concept (1992) with the number of items of each instrument as much as 40. Reliability value of instrument were calculated using Cronbach Alpa formula of 0,886. The data were analyzed by descriptive statistic using mean, mean, average, and standard deviation. Descriptions go through the categorization of normal distribution by category: very high, high, medium, low, and very low. The findings of this study show that 41% of parents/guardians have support for children's learning in very high category, 45,1% of high category, and 12,9% of moderate category. Based on the opinion of the students, there are 45,1% students who believe that the carrying capacity of the parents/guardian to the learning of the child is in very high category, 45,1% of the high category, 6,4% of the medium category, and found 3,2% of the low category. These findings serve as a basis for providing trajectory to parents to improve parental support systems for child learning.